WRITING DIALOGUE FOR ROLEPLAY - Cecep Maulana; Bambang Panca Syahputra (Smart Education, 2023)
Abstract: This research is based on improving writing skills, especially on how to make dialogues and use role playing in the classroom. The main purpose of this research is to follow up on student understanding in writing dialogue and using role playing for STMIK Royal students, especially the SI 1L class in the 2022/2023 academic year. In STMIK Royal student learning for writing skills, students have problems especially with writing because they are lazy to do this activity. so that lecturers give high attention and motivation and also change good material to them. This research method is classroom action research (CAR). The data in this study uses percentage analysis. The respondents of this study were students at STMIK Royal Kisaran which consisted of 35 students. Based on the results of data analysis, there was an increase in achievement in writing dialogue and using role playing by showing the pre-test and post-test which consisted of intervals, results, the number of students' frequency and presentation of the pre-test and post-test showed a very good increase of around 98 % the percentage where the scores that get very good grades are around 18 students or around 51% while good grades are around 15 students or around 42% while sufficient grades get 2 students with a percentage of around 05% while low grades and failing approx.Keywords: writing dialogue; for role play. Abstrak: Penelitian ini didasarkan pada peningkatan keterampilan menulis, khususnya tentang bagaimana membuat dialog dan menggunakan bermain peran di dalam kelas. tujuan utama dari penelitian ini adalah untuk menindaklanjuti pemahaman mahasiswa dalam menulis dialog dan menggu bermain peran untuk mahasiswa STMIK Royal, khususnya kelas SI 1L pada tahun akademik 2022/2023. Dalam pembelajaran mahasiswa STMIK Royal untuk keterampilan menulis, para mahasiswa memiliki masalah terutama tentang menulis karena mereka malas melakukan kegiatan ini. sehingga dosen memberikan perhatian dan motivasi tinggi dan juga mengubah materi yang baik kepada mereka. Metode penelitian ini adalah penelitian tindakan kelas (PTK). Data dalam penelitian ini menggunakan analisis persentase. Responden penelitian ini adalah mahasiswa di STMIK Royal Kisaran yang terdiri dari 35 mahasiswa. Berdasarkan hasil analisis data, terdapat peningkatan prestasi menulis dialog dan menggunakan bermain peran dengan menunjukkan pre-test dan post-test yang terdiri dari Interval, Hasil, jumlah frekuensi siswa dan presentasi dari pre-test dan post-test menunjukkan peningkatan yang sangat baik sekitar 98% persentase dimana nilai yang mendapatkan nilai sangat baik sekitar 18 siswa atau sekitar 51% sedangkan nilai yang baik sekitar 15 siswa atau sekitar 42% sedangkan nilai yang cukup mendapat 2 siswa dengan persentase sekitar 05% sedangkan nilai yang rendah dan gagal sekitar.Kata kunci: menulis dialog; untuk bermain peran.